2019
DOI: 10.1111/cpr.12716
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG15: A new budding star in human cancers

Abstract: Objectives Long non‐coding RNAs (lncRNAs) represent an important group of non‐coding RNAs (ncRNAs) with more than 200 nucleotides in length that are transcribed from the so‐called genomic “dark matter.” Mounting evidence has shown that lncRNAs have manifested a paramount function in the pathophysiology of human diseases, especially in the pathogenesis and progression of cancers. Despite the exponential growth in lncRNA publications, our understanding of regulatory mechanism of lncRNAs is still limited, and a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 149 publications
(615 reference statements)
0
26
0
Order By: Relevance
“…To further clarify the relationship between linc01503 level and survival outcome of patients with GC, the Kaplan‐Meier plotter (KmPlot), which has been used in various cancers, was implicated in this research (http://kmplot.com/analysis) 18‐22 …”
Section: Resultsmentioning
confidence: 99%
“…To further clarify the relationship between linc01503 level and survival outcome of patients with GC, the Kaplan‐Meier plotter (KmPlot), which has been used in various cancers, was implicated in this research (http://kmplot.com/analysis) 18‐22 …”
Section: Resultsmentioning
confidence: 99%
“…Aberrant lncRNA expression has been validated to be closely linked with cell death in ischemic stroke progression [ 5 ]. SNHG15 has been widely identified as an onco-lncRNA in multiple cancer types [ 12 ], but its role in other diseases is less studied. The present study validated that SNHG15 is highly expressed in MCAO-treated mice and OGD-treated N2a cells, which aggravates neuronal injury after ischemic stroke with the involvement of the miR-18a/CXCL13/ERK/MEK axis.…”
Section: Discussionmentioning
confidence: 99%
“…Several such networks have been validated to fulfill key functions in neuron apoptosis and nerve injury after ischemic stroke [ 10 , 11 ]. Small nucleolar RNA host gene 15 (SNHG15) is a strongly conserved lncRNA located at 7p13 with 860 bp in length, and its functions in tumor progression in several human cancers have been well documented [ 12 ]. SNHG15 has been noted to promote glioma progression [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In HCC, moreover, snoRNA SNORD113-1 was also found to be significantly downregulated and functions as a tumor suppressor role [ 23 ]. SNHG16, SNORD76, and SnoU2_19 can regulate the development of HCC through Wnt/ β -catenin signaling pathway [ 29 ]. Therefore, these indicated that some specific snoRNAs had underlying abilities to serve as biomarker for clinical evaluation of HCC patients.…”
Section: Discussionmentioning
confidence: 99%